Measuring Pulsatile Flow in Cerebral Arteries Using 4D Phase-Contrast MR Imaging - Wåhlin, A. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: 4D PCMRI can be used to quantify pulsatile hemodynamics in multiple cerebral arteries. The aim of this study was to compare 4D PCMRI and 2D PCMRI for assessments of pulsatile hemodynamics in major cerebral arteries. MATERIALS AND METHODS: We scanned the internal carotid artery, the anterior cerebral artery, the basilar artery, and the middle cerebral artery in 10 subjects with a single 4D and multiple 2D PCMRI acquisitions by use of a 3T system and a 32-channel head coil. We assessed the agreement regarding net flow and the volume of arterial pulsatility (ΔV) for all vessels. RESULTS: 2D and 4D PCMRI produced highly correlated results, with r = 0.86 and r = 0.95 for ΔV and net flow, respectively (n = 69 vessels). These values increased to r = 0.93 and r = 0.97, respectively, during investigation of a subset of measurements with <5% variation in heart rate between the 4D and 2D acquisition (n = 31 vessels). Significant differences were found for ICA and MCA net flow (P = .004 and P < .001, respectively) and MCA ΔV (P = .006). However, these differences were attenuated and no longer significant when the subset with stable heart rate (n = 31 vessels) was analyzed. CONCLUSIONS: 4D PCMRI provides a powerful methodology to measure pulsatility of the larger cerebral arteries from a single acquisition. A large part of differences between measurements was attributed to physiologic variations. The results were consistent with 2D PCMRI.